2019
DOI: 10.3390/polym11050848
|View full text |Cite
|
Sign up to set email alerts
|

Changes on the Structural and Physicochemical Properties of Conjugates Prepared by the Maillard Reaction of Black Bean Protein Isolates and Glucose with Ultrasound Pretreatment

Abstract: The conjugates of black bean protein isolate (BBPI) and glucose (G) were prepared via the wet heating Maillard reaction with ultrasound pretreatment. The physicochemical properties of UBBPI-G conjugates prepared by ultrasound pretreatment Maillard reaction had been compared with classical Maillard reaction (BBPI-G). The reaction rate between BBPI and glucose was speeded up by ultrasound pretreatment. A degree of glycation (DG) of 20.49 was achieved by 2 h treatment for UBBPI-G, whereas 5 h was required using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…As provided in Table 1, compared with BBPI, the ordered structure (α-helix structure + β-sheet structure) content of BBPI-G decreased significantly, while the disordered structure (β-turn structure + random coil structure) content increased significantly. The results showed that the secondary structure of BBPI changed significantly after Maillard reaction and turned to a more disordered direction [14]. This may be due to the fact that the interaction between BBPI and polysaccharide molecules affected the hydrogen bonding and van der Waals forces between molecules, which broke up the stability of the protein secondary structure [29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As provided in Table 1, compared with BBPI, the ordered structure (α-helix structure + β-sheet structure) content of BBPI-G decreased significantly, while the disordered structure (β-turn structure + random coil structure) content increased significantly. The results showed that the secondary structure of BBPI changed significantly after Maillard reaction and turned to a more disordered direction [14]. This may be due to the fact that the interaction between BBPI and polysaccharide molecules affected the hydrogen bonding and van der Waals forces between molecules, which broke up the stability of the protein secondary structure [29].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3, after the Maillard reaction, the EAI and ESI of BBPI increased from 42.53 m 2 /g and 18.98 min to 52.82 m 2 /g and 22.44 min, respectively. This may be because glucose was a hydrophilic sugar with a polyhydroxy structure and the –OH group of glucose in BBPI-G promoted the adsorption between proteins and water molecules through its hydrogen bonding ability [14]. At the same time, based on the infrared data above, we could obtain that the covalent grafting of the sugar chain led the protein structure to be more disordered, which optimized the emulsification performance [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different researchers affirm that glycation via Maillard reaction could cause structural changes in protein molecules, which could generate a wide range of compounds or Maillard reaction products (MRP), which would lead to the formation of conjugates and that these could contribute to the generation or increase of antioxidant capacity [59].…”
Section: Antioxidant Capacitymentioning
confidence: 99%